2011
DOI: 10.1097/hnp.0b013e3182157c19
|View full text |Cite
|
Sign up to set email alerts
|

Considering Elderly Competence When Consenting to Treatment

Abstract: The older adult population is growing rapidly with various comorbidities for health care providers to consider. Additional treatments and procedures are often implemented to care for the aging adults with comorbidities. Informed consent is involved with any invasive procedure or treatment and requires a cognizant patient who can give verbal or written consent, often a challenge for caregivers of the elderly. This article provides examples of assessment tools to utilize while assessing the older adults. Increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Of the 80 articles, 16 were essay-type articles 16,20,23,27,30,33,37,42,64,65,67,68,71,72,81,91 ; 7 were surveys 18,19,46,47,73,75,85 ; and 57 were research articles consisting of case studies and case reports, follow-up studies, cross-sectional studies, case-control and cohort studies, randomized trials, and systematic reviews. 1315,17,21,22,2426,28,29,31,32,34–36,3841,4345,4863,66,69,70,74,7680,8284,8690,92 The studies reviewed were from a variety of international settings: United States (n = 33); United Kingdom (n = 7); France (n = 5); the Netherlands (n = 5); Spain (n = 3); and Canada, Sweden, Finland, Germany, Switzerland, Turkey, Hong Kong, Scotland, Norway, Italy, South Africa, Israel, Korea, Austria, and Nigeria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 80 articles, 16 were essay-type articles 16,20,23,27,30,33,37,42,64,65,67,68,71,72,81,91 ; 7 were surveys 18,19,46,47,73,75,85 ; and 57 were research articles consisting of case studies and case reports, follow-up studies, cross-sectional studies, case-control and cohort studies, randomized trials, and systematic reviews. 1315,17,21,22,2426,28,29,31,32,34–36,3841,4345,4863,66,69,70,74,7680,8284,8690,92 The studies reviewed were from a variety of international settings: United States (n = 33); United Kingdom (n = 7); France (n = 5); the Netherlands (n = 5); Spain (n = 3); and Canada, Sweden, Finland, Germany, Switzerland, Turkey, Hong Kong, Scotland, Norway, Italy, South Africa, Israel, Korea, Austria, and Nigeria.…”
Section: Resultsmentioning
confidence: 99%
“…13,15,32,38,87 The authors in most of these articles favored the MMSE and MacCAT over others. Investigators discussed concepts related to declining capacity and advance directives more thoroughly in the medical literature 20,23,39,42,61,67 than in the dental literature. Investigators identified decision making and preserving patient autonomy as substantial ethical concerns arising in cases of medical emergencies.…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in healthcare have also resulted in increased life expectancy for those with intellectual disabilities [11], and those with acquired brain injuries such as stroke [12][14]. Decision-making for these individuals can present a number of practical, ethical and legal challenges [15]–[17]. It is particularly when questions of capacity arise with respect to the maintenance of life, or the end of life, as exemplified by decisions concerning artificial means for maintaining nutrition, that making healthcare choices may be the most difficult and contentious.…”
Section: Introductionmentioning
confidence: 99%